ANALISIS PENERAPAN SISTEM INFORMASI MANAJEMEN KEPEGAWAIAN (SIMPEG) DALAM PENETAPAN NOMINATIF SELEKSI TALENT SCOUTING PNS PROVINSI JAWA TENGAH - Elisa Hikmatun Rizkia; wahid Abdulrahman (Journal of Politic and Government Studies, 2026)
The Personnel Management Information System (SIMPEG) is an e-Government accreditation that stores personnel data through digitization, SIMPEG supports the process of determining nominative talent scouting civil servants as the basis for determining prospective selection participants, so that the importance of the quality of personnel data that requires accurate, up to-date, and integrated data. This study uses a qualitative method with data collection techniques through interviews, observation and documentation. Data was analyzed with an approach based on the quality of SIMPEG information, namely timely, accurate, concise, relevant and complete, as well as analysis of supporting and inhibiting factors using e Government indicators, namely support, capacity and value. The results of this study show that SIMPEG has played an important role in accelerating the nominative determination process and providing structured data that meets the concise, relevant, and fairly complete aspects. However, there are obstacles related to timeliness due to limited server infrastructure, data accuracy that still depends on the discipline of ASN to update data, and uncertain budget availability for system development. The main supporting factors are the commitment of the manager's human resources and the perceived efficiency benefits, while the main obstacles are regulations that are not yet specific, limited budgets, and infrastructure that is not yet optimal. The conclusion of this study is that the implementation of SIMPEG has made a positive contribution in supporting the determination of nominative talent scouting, but there is still a need for improvement in the aspects of infrastructure, regulations, and data update mechanisms. The suggestions submitted include: (1) a structured and continuous supervision mechanism, such as the implementation of SOPs, periodic evaluation and auditing of personnel data, as well as the enforcement of ASN data update discipline (2) the implementation of a scheduled data update reminder mechanism.